ANALISIS KESALAHAN BERBAHASA INDONESIA DI SEKOLAH DASAR - Marwan Pandeangan; Jangkontua Siburian; Livia Olga Indah Sari; Novita Sari (Universitas Negeri Medan, 2020)
This study aims to describe the mistakes in Indonesian language made by students in elementary schools in general. The focus of the study was conducted on language errors in writing skills in elementary school. This type of research is descriptive research. The data source in this research is searching relevant journals. The analysis technique used in analyzing language errors is qualitative data analysis techniques. The results showed that there were student errors in writing including: spelling mistakes (errors in writing basic words, mistakes in using capital letters, mistakes in writing prefixes, mistakes in writing prepositions, mistakes in abbreviated writing, and errors in punctuation), errors in word selection (use of words speech), and mistakes in sentence construction (incomplete sentences, ineffective sentences, and sentences containing interference). Thus, students 'mistakes in writing must be minimized as an effort to improve students' writing skills in elementary school.Keywords: Language errors, spelling, word selection, sentence organization